"It was emotional"—A group for people with learning disabilities to talk about end of life. (11th February 2020) - Reilly, Deirdre Emer; Raymond, Kathryn; O'Donnell, Chris
Accessible summary: People with a learning disability told us people do not talk to them about death. This is about a group we ran to help people learn about death and the end of their life. The group talked about people who had died and what might happen when they die. People in the group wanted help to talk to their own parents about what might happen when their parents die. People did not have enough information about the cost of funerals. The group was important as it helped people to learn. Some people made plans for what they would like to happen when they die. Abstract: Background: Academic research and reports from healthcare professionals tell us people with learning disabilities are not routinely supported to learn about end‐of‐life issues or make plans for the end of their lives. Materials: Questionnaires were used to check how much people knew. Accessible symbols were used to help people understand end‐of‐life specific terms. Method: Partnering with a charity, three sessions were held in three consecutive weeks to ask people in a convened group what they wanted to know and help them learn. The sessions supported people to start creating their own plans for funerals, where they want to die and what should happen with their possessions. Results: This group had between 21 and 23 ( N  = 23) attendees each week and all except one person came back after the first week. The participants were keen to highlight what they did not know and learn about end‐of‐life issues. They also wanted support to plan for the end of their lives and their parents' lives, and the group tried to provide information and support on these topics. Conclusion: This group was a valuable exercise that was very much needed by local people with learning disabilities. The group will run again and should be offered in other areas. Groups of this kind can offer unmet needs that are highlighted by national guidance in England, UK such as the NHS long‐term plan and the Learning Disability Mortality Review Programme.